Investigations into the genetics of atopic dermatitis in guide dogs - Lewis, Thomas (2024)
Canine atopic dermatitis (cAD) is a common pruritic, inflammatory condition resulting from an immune response to heightened allergen sensitivity that usually manifests in the skin leading to an ‘itch-scratch’ cycle. Differential prevalence among breeds points to genetic variation in predisposition, and various environmental influences have been reported. It is the most common cause of withdrawals among in-training and working guide dogs, representing a major cost to the organisation not just from withdrawals but also in the treatment and management of affected dogs, as well as a major welfare burden on the affected dogs themselves.